1989
DOI: 10.1136/ard.48.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal brucellosis in Iraqi patients.

Abstract: SUMMARY The clinical features of 21 episodes of skeletal brucellosis in 17 Iraqi patients are reported. Six had monarthritis of a large joint, six had spondylitis, and five had spondarthritis. Brucellosis remains a major health problem in Iraq. The disease is transmitted to man through the ingestion of unpasteurised milk or milk products but can also be acquired through physical contact.Key words: Brucella abortus, monarthritis, spondylitis, spondarthritis. Patients and methods ResultsSeventeen consecutive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
2
0
4
Order By: Relevance
“…In adults, a recent randomized study suggested an adequate (but not superior) response rate comparable to the WHO-recommended regimens, although the treatment duration was extended [ 46 ]. Past studies have produced contradicting results, with relapse rates ranging from 0% to 30% (TMP-SMX combinations with tetracycline) [ 25 , 47 ].…”
Section: Tmp-smx-containing Regimensmentioning
confidence: 99%
“…In adults, a recent randomized study suggested an adequate (but not superior) response rate comparable to the WHO-recommended regimens, although the treatment duration was extended [ 46 ]. Past studies have produced contradicting results, with relapse rates ranging from 0% to 30% (TMP-SMX combinations with tetracycline) [ 25 , 47 ].…”
Section: Tmp-smx-containing Regimensmentioning
confidence: 99%
“…L'atteinte des grosses articulations périphériques représente un fort pourcentage des atteintes ostéoarticulaires de la brucellose, pourcentage qui est néanmoins variable dans les différen-tes séries [15,16,19,20]. L'atteinte articulaire périphérique est la règle chez l'enfant [21,22] et dans la brucellose liée à B. abortus [23].…”
Section: Arthrites Périphériquesunclassified
“…L'atteinte de la sacro-iliaque est fréquente et peut représen-ter un quart à la moitié de l'ensemble des atteintes ostéoarticu-laires de la brucellose [16,17,19,20,26,31,32]. À l'inverse, l'atteinte sacro-iliaque est rare chez l'enfant [21,22] et lors des infections à B. abortus ou à B. suis [33].…”
Section: Sacro-iliiteunclassified
See 1 more Smart Citation
“…Die uni-oder bilaterale Sakroileitis ist häufig. Bei den peripheren Arthritiden stehen Hüft-und Kniegelenk im Vordergrund (Al-Rawi et al 1989;Gotuzzo et al 1982). Die sternoklavikuläre Beteiligung ist in Einzelberichten beschrieben worden (Colmenero et al 1991).…”
Section: Radiologische Symptomatikunclassified